Comportamento de duas variedades de soja em diferentes espaçamentos de plantio e níveis de adubação, no Triângulo Mineiro - Silva Reis, Múcio; Vieira, Clibas; S Sediyama, Carlos; M S Andrade, Antônio; de Almeida Filho, José; Braga, José Mário (Revista Ceres, 2025)
In order to verify the performance of the soybean varieties 'UFV-1' and 'IAC-2' in different row spacings and levels of fertilization, a study was carried out in the Triângulo Mineiro area of the state of Minas Gerais. Five experiments were conducted, two in fertile terra roxa soil and three in cerrado soil (medium fertility).